A preliminary exploration of the effect of concurrent antidepressant medication on responses to high-frequency repetitive transcranial magnetic stimulation (rTMS) in severe, enduring anorexia nervosa - Bethan Dalton; Jessica McClelland; Savani Bartholdy; Maria Kekic; Iain C. Campbell; Ulrike Schmidt (Journal of Eating Disorders, 2021)
Abstract Background Repetitive transcranial magnetic stimulation (rTMS) is a promising treatment option for people with severe, enduring anorexia nervosa (SE-AN). As depression is often comorbid with AN, antidepressant medication is commonly prescribed to this patient group. Concurrent antidepressant medications may affect the rTMS treatment response. Therefore, in a secondary analysis of data from a feasibility trial, we explored the effect of antidepressant medication on responses to rTMS in people with SE-AN. Methods Twenty-six participants with SE-AN received 20 sessions (over 4 weeks) of neuronavigated high-frequency real rTMS to the left dorsolateral prefrontal cortex. Eating disorder (ED) and general psychopathology symptoms were assessed at baseline, post-treatment and at a 4-month follow-up. Results Participants taking antidepressants (n = 16) for the duration of the rTMS treatment had a greater reduction in ED symptoms at the 4-month follow-up, compared to those not taking antidepressants (n = 10). Antidepressant status was not however associated with significant changes in mood outcomes. Conclusions In people with SE-AN receiving rTMS treatment, preliminary findings suggest a potential synergistic effect of antidepressant medication in reducing ED symptomatology. There was however no associated reduction in affective symptoms i.e., the effect does not seem to be related to changes in mood. The sample in this exploratory study was small and heterogenous. However, the preliminary results provide a basis for hypothesis generation for future studies.